Groundwater quality analysis using the weighted arithmetic water quality index at the elementary school - Lathifah Hanum; Margaretha Widyastuti (Sustainable Urban Development and Environmental Impact Journal, 2026)
Background: Children are a vulnerable group exposed to water pollution. Elementary schools in Kapanewon Prambanan, have experienced complaints regarding water quality. Therefore, this study aims to determine the water quality in elementary schools in Kapanewon Prambanan compared to the quality standards according to PERMENKES Number 2 of 2023 and to calculate the water quality index using the Weighted Arithmatic Water Quality Index (WAWQI) method. Method: The parameters tested were pH, Total Dissolved Solid (TDS), turbidity, nitrate, iron, and E.Coli. Measurements were carried out directly in the field at 12 sample points and testing was carried out in the laboratory. Determination of sample points was based on land use, Groundwater Basin (CAT) areas, geology, soil type, and complaints about water quality problems. Findings: Based on WAWQI calculations, it can be seen that the water quality at Kapanewon Prambanan elementary school is divided into two classes, namely very good and not suitable for consumption needs. WAWQI values range from 7.51 to 3105.82. Based on a comparison of the measurement results with the PERMENKES quality standards Number 2 of 2023, there are four sample points that exceed the quality standards for turbidity parameters, two points for TDS parameters, three sample points for nitrate parameters, and ten for E.Coli parameters. Conclusion: The WQI value at Kapanewon Prambanan Elementary School, which is divided into two classes, namely not suitable for consumption needs and very good is directly proportional to the distance of the well to the septic tank. Schools with very good water quality have a distance that meets the standard, which is more than 10 meters. Novelty/Originality of this article: This study is expected to be able to increase attention regarding the study of water quality in schools, especially in Indonesia, which is currently still rarely done.